answersLogoWhite

0

What is 12 divided by 10 plus 1?

Updated: 4/28/2022
User Avatar

Wiki User

9y ago

Best Answer

12/10 + 1 = 2.2

User Avatar

Wiki User

9y ago
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

➡️
See all cards
3.82
3068 Reviews

Add your answer:

Earn +20 pts
Q: What is 12 divided by 10 plus 1?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 20 divided by 10 plus 10?

20/10 + 10 = 12 20/(10 + 10) = 1


What is the answer 10 plus 2 divided by 4 times 3?

10+2÷(4x3)= 10+2÷ (12)= 12÷(12)= 1


What is 12tenths plus 9tenth?

12 + 9 = 21. 21/10 =2 and 1/10 (21 divided by 10).


What is 8 plus 4 minus 12 divided by 1?

8 plus 4 minus 12 divided by 1 is 0.


Take the number 30divide it by 12and then add 10what do you get?

30 divided by 12 plus 10 = 12 1/2 (12.5)


2 plus 10 divided 2 x 6 equals 1?

It does. Follow order of operations (BEDMAS): (2+10)/(2x6), brackets first (12)/(12), no exponents 12/12 = 1 by division


What is 7 divided by 10 plus 1 divided by 14?

0.77142857142


What is 10 out of 12 out of 10?

You're essentially asking what is 10/12/10 (that is ten divided by twelve divided by ten.10 ÷ 12 = .8333....8333 ÷ 10 = .08333....


What divided by -3 plus 7 equals 10?

-1


Is it ok if on 109 divided by 9 be 12 plus 1?

109/9 = 12 with a remainder of 1


What is 12 times 8 divided by 9 plus 1?

It is (12*8)/(9+1) = 9.6


What is 5 divided by 6 times 1 divided by 10 plus 2 divided by 3 divided by 4 divided by 11?

(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12